Analysis of curaua/glass hybrid interlayer laminates - Angrizani, Clarissa C.; Cioffi, Maria O. H. [UNESP]; Zattera, Ademir J.; Amico, Sandro C. (Sage Publications Ltd, 2014)
This study compares the mechanical properties of curaua, glass and hybrid curaua/glass laminates evaluated experimentally with those obtained theoretically using commercial software for composites. Hybrids laminates were produced varying the fiber layer stacking sequence with the aim of optimizing the combination of vegetable and synthetic fibers. Composites were compression molded using eight layers of glass and/or curaua fiber mats and mechanically tested as per ASTM standards. The combination of curaua and glass fibers produced a material with intermediate properties and, depending on the type of mechanical loading and the stacking sequence, some hybrids showed properties close to the pure glass fiber composites. Furthermore, hybrid composites with glass layers closer to the surfaces showed the best overall results.
Keywords: vegetable fiber; composites; curaua; Hybrid; micromechanics